2012
DOI: 10.1097/rhu.0b013e31824e1f6f
|View full text |Cite
|
Sign up to set email alerts
|

Living With Gout in New Zealand

Abstract: There were substantial gaps in the knowledge about gout and its causes and management. All healthcare providers could help identify patients with suboptimal knowledge and improve the management of gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…This has clear implications for the quality and safety of medicines use. In line with earlier work, [ 19 , 20 ] this study revealed lack of knowledge related to the appropriate NSAID dosing for an acute gout flare and confusion around NSAID generic and brand names. Some patients also lacked a clear understanding of the specific and unusual issues around the initiation of allopurinol therapy; an area which has been previously identified as a source of patient confusion [ 19 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This has clear implications for the quality and safety of medicines use. In line with earlier work, [ 19 , 20 ] this study revealed lack of knowledge related to the appropriate NSAID dosing for an acute gout flare and confusion around NSAID generic and brand names. Some patients also lacked a clear understanding of the specific and unusual issues around the initiation of allopurinol therapy; an area which has been previously identified as a source of patient confusion [ 19 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
“…To be considered for preventive treatment patients will have been previously symptomatic, although the level of pain experienced by an individual may vary widely. It is therefore not surprising that here, and in previous studies, [ 19 , 23 ] patients have admitted to failing to take medicines both unintentionally (they were unaware of how it should be taken or simply forgot) and intentionally (they had no desire to take a medicine every day) [ 19 , 23 ]. It is notable that one patient continued to take a medicine to treat gout despite the fact that it exacerbated a co-morbid condition, identifying that patient values and judgments around medicine side-effects may differ from their practitioner’s.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, difficulties can develop where structural foot changes attributable to the arthritis progression make it problematic for patients to find appropriate shoes that are capable of accommodating their foot deformities. Martini et al [ 19 ] reported that people with gout, who experienced symptoms in their lower extremities, were unable to put their shoes on or walk with ease and subsequently stayed at home. To get around the home, they limped, used crutches, or relied on family support to be mobile [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Martini et al [ 19 ] reported that people with gout, who experienced symptoms in their lower extremities, were unable to put their shoes on or walk with ease and subsequently stayed at home. To get around the home, they limped, used crutches, or relied on family support to be mobile [ 19 ]. For people with RA-related foot problems, footwear difficulties can be the source of considerable distress and reinforce negative feelings associated with arthritic foot changes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%